Who was Princess Diana? - Labrecque, Ellen; Hoare, Jerry (New York : Grosset & Dunlap, 2017)
A shy twenty-year-old girl stepped out of a horse-drawn coach and into the world spotlight, capturing the imagination of millions as a real life fairytale princess. Although the storybook marriage didn't have a happy ending, Diana learned to use her fame as a way to champion charitable causes near to her heart. She became the People's Princess by humanizing the image of the royal family and showing care and concern for all people, including the homeless, the sick, and others in need.
Includes bibliographical references (page 108).
6.2
3-6
920L
Keywords: Diana, -- Princess of Wales, -- 1961-1997 -- Juvenile literature; Princesses -- Great Britain -- Biography -- Juvenile literature; Diana, -- Princess of Wales, -- 1961-1997.; Princesses; Women -- Great Britain -- Biography; Diana, -- Princess of Wales, -- 1961-1997.; Princesses -- Great Britain -- Biography; Women -- Great Britain -- Biography; Biographies